PENGARUH KOMPETENSI, PENGALAMAN AUDIT, TEKANAN WAKTU, SKEPTISME PROFESIONAL TERHADAP KEMAMPUAN AUDITOR MENDETEKSI FRAUD LAPORAN KEUANGAN - Iman Firmansyah; Lesia Fatma Ginoga; Saleh, Rahmat (Jurnal Bisnis Terapan, 2024)
This objective of this research to empirically analyze the influence of competency, time pressure, audit experience, and professional skepticism on auditor ability in detecting fraud on financial statements. The population in this research are auditors who worked on Public Accounting Firm in DKI Jakarta area. Primary data collection method used is questionnaire method. The data are analyzed by using Moderate Regression Analyze (MRA). The analytical tool used to test the hypothesis is SPSS 25. The result showed that Competency, Audit Experience, and Proffesional Skepticism have a positive impact on auditors ability of fraud detection. Value of the coefficient of determination indicates that together the Competency, Time Pressure, Audit Experience and Proffesional Skepticism contribute to dependent variable (Auditors Ability of Fraud Detection in Financial Statement) of 84,8% while the remaining 15,2% are influenced by other autside factor model. Copyright © 2024 by Authors, Published by Jurnal Bisnis Terapan. This work is licensed under a Creative Commons. Attribution-ShareAlike 4.0 International License